PENGARUH STRATEGI CUSTOMER BONDING TERHADAP CUSTOMERSATISFACTION DAN CUSTOMER LOYALTY PADAPT. BANK RAKYATINDONESIA (PERSERO) TBK.(Survey Pada Nasabah Tabungan Britama KantorCabang Teluk Kuantan) - Efni, Yulia (Jurnal Tepak Manajemen Bisnis, 2016)
This study aims to determine the effect on each stage of customer bonding consisting ofawareness, identity, relationship, community, and advocacy bonding to customer satisfactionand customer loyalty as well as the influence of customer satisfaction on customer loyalty.Collecting data using questionnaires, from 270 customers Britama determined using purposivesampling method. Data analysis tools using structural equation modeling studies, which meetthe assumptions of normality and there is no outlier.The results showed that every phase ofcustomer bonding has a positive and significant impact on customer satisfaction and customerloyalty. Where awareness, identity, relationship, community, and advocacy bonding effect oncustomer satisfaction and customer loyalty. Then the relationship between customersatisfaction to customer loyalty is also shown to have a positive and significant impact.Various things need to be done to strengthen customer bonding, further enhancing customersatisfaction and customer loyalty. It is with regard to advertising, promotional programs,Corporate Social Responsibility for the general public, content and updating the website, aswell as community focused on the customer.